(untitled) (Research, Society and Development, 2022)
In recent years, due to a better understanding of caries pathology and advances in dental materials, the use of non-invasive and minimally invasive techniques that delay or avoid the need for traditional restorations has gained importance. Objective: To present an update of concepts of minimally invasive dentistry in the treatment of dental caries. Methodology: The present investigation had an approach based on a literary review, allowing the comparison of studies by different authors on minimally invasive dentistry. Conclusion: Currently, minimally invasive dentistry has become the most common philosophy of dental treatment. The possibility of its inclusion is due in large part to the advent of new dental materials that adhere to the dental structure, more conservative methods for a healthy dental structure, achieving a treatment with a less invasive surgical approach and minimal removal of healthy tissue.